PENGARUH PERCEIVED ORGANIZATIONAL SUPPORT DAN KEADILAN ORGANISASIONAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR MELALUI KEPUASAN KERJA (STUDI PADA KARYAWAN PT PURNAMA INDONESIA SIDOARJO) - AMALIA FADLILAH, CITRA; SURJANTI, JUN (Jurnal Ilmu Manajemen (JIM), 2018)
This organizational citizenship behavior is one factor that still becomes a problem for the company. Perceived organizational support, organizational justice and job satisfaction can also influence the organizational citizenship behavior. This study aims to analyze the effect of perceived organizational support and organizational justice on organizational citizenship behavior through job satisfaction (study of PT Purnama Indonesias employees). In the study that conducted at PT. Purnama Indonesia used saturated samples and taken 49 employees as respondents through questionnaire methods and interviews. The study was conducted by means of quantitative research by using PLS 3.0 software. The results of this study prove that perceived organizational support has a negatif effect on organizational citizenship behavior, while organizational justice has a positive effect on organizational citizenship behavior. Perceived organizational support has a negatif effect on job satisfaction, organizational justice has a positive effect job satisfaction, job satisfaction has a positive effect on organizational citizenship behavior. Job satisfaction as an intervening variabel cannot affect perceived organizational support towards organizational citizenship behavior and job satisfaction as an intervening variabel cannot affect organizational justice towards organizational citizenship behavior. Keywords: job satisfaction; perceived organizational support; organizational citizenship behavior; organizational justice